O processo eleitoral na era digital - Ferreira Neto, Arthur Leopoldino (2024)
The development of Information and Communication Technologies (ICT) has profoundly altered the governance landscape and forms of social interaction, exerting effects on political participation. This thesis addresses the connection between the electoral process and the Internet, analyzing the determinants of electoral participation in Brazil. The study begins with the state of the art in Electoral Law, examining the role of political actors and the procedures involved in electoral operations, seeking to comprehend the contributions brought by the Internet to this dynamic. Subsequently, we analyze how the Internet has been used in electoral processes by political actors, exploring its limits and possibilities with the aim of assessing the potential of the Internet to invigorate democracy and enhance civic engagement. We also present regulatory proposals to improve the utilization of Internet tools and potentials during the electoral process, and finally, we highlight some practices of such usage in other countries. The proposed analytical framework reveals that the expansion of the Internet and its social media, along with the freedom found in its virtual space, has a positive effect on electoral participation